DESIGNATION OF METEOROLOGICAL PARAMETERS USING GPS SATELLITE TECHNIQUE IN A FLIGHT EXPERIMENT AT THE DĘBLIN MILITARY AERODROME - Kamil KRASUSKI; Małgorzata KIRSCHENSTEIN (Scientific Journal of Silesian University of Technology. Series Transport)
This paper presents research results on the determination of meteorological parameters utilising the GPS satellite technique. The meteorological parameters were designated using Standard Atmosphere (SA) and UNB3m empirical models. The research experiment was realised during a flight test at the Dęblin military aerodrome. In the flight test, the Cessna 172 plane was used. The values of meteorological parameters (for example, temperature, pressure and relative humidity) from the troposphere empirical models were presented and compared in the paper. In addition, the values of the meteorological parameters were estimated at flight attitude. The range of the flight attitude was between 150 and 700 m. The precision position of the aircraft in vertical frame was determinated using the RTK-OTF differential technique. The mean difference of temperature between the SA and UNB3m models is equal to -5.7°C with the RMS bias approximately 0.2°C. The mean difference of pressure between the SA and UNB3m models equals -1.0 hPa with the RMS bias of approximately 0.3 hPa. The mean difference of relative humidity between the SA and UNB3m models equals 25.5%, with the RMS bias approximately 0.6%. On paper, the values of meteorological data from the SA and UNB3m models were compared with true results interpolated from SYNOP message. In research, the three SYNOP stations, that is, Kozienice, Deblin/Irena and Lublin Radawiec were used for interpolation of the real meteorological data. The difference between empirical and interpolated meteorological data were presented in this paper. The accuracy of the designation of temperature is better in the SA model rather than the UNB3m model. The accuracy of the designation of pressure was relatively low in both models, SA and UNB3m. On the other hand, the accuracy of the designation of relative humidity was better in the UNB3m model than the SA model.